Multilevel system of personnel training at metallurgical enterprises - Mamych, Andriy; Bohdanov, Serhii (Management and Entrepreneurship: Trends of Development, 2017)
The relevance of the topic under investigation is due to the general need to disclose the optimal system of training personnel at metallurgical plants, taking into account the increase in the efficiency of enterprises. The subject of the study are the theoretical and methodological foundations of training and applied aspects of creating better conditions for this. Purpose: study on the importance of the impact of training on the effectiveness of the enterprise. Design/methodology/approach: historical, analytical and comparative methods used by the system and structural and functional approaches. Findings: It was found that the modern economic landscape is characterized by a complex system of division of labor with a large number of different professions, resulting in a system of professional orientation to act as a regulator that directs individual abilities for further development and retraining. To achieve maximum effect, it is necessary to introduce a multilevel training system, consisting of: Organization of training: plan, budget and choice of knowledge providers; Professional training; Managers and specialists training; Interaction with educational institutions; Assessment of the effectiveness and efficiency of training Therefore, recommendations are made on the study of the training process and the training of personnel, taking into account the different and similar concepts of domestic and foreign industrial enterprises. Research limitations/implications: The paper studies the results caused by regarding the creation of a multilevel continuous system of training personnel. Originality/value: Such knowledge will help to the growth of competence of the mill’s employees and the economic performance of the enterprise in general